Assessment and management of iron overload in β‐thalassaemia major patients during the 21st century: a real‐life experience from the Italian Webthal project. (18th April 2013) - Piga, Antonio; Longo, Filomena; Musallam, Khaled M.; Cappellini, Maria Domenica; Forni, Gian Luca; Quarta, Giovanni; Chiavilli, Francesco; Commendatore, Francesca; Mulas, Sergio; Caruso, Vincenzo; Galanello, Renzo
Summary We conducted a cross‐sectional study on 924 β‐thalassaemia major patients (mean age 30·1 years) treated at nine Italian centres using the webthal software, to evaluate real‐life application of iron overload assessment and management standards. Serum ferritin <2500 ng/ml was a risk factor for never having liver iron concentration (LIC) measurement, while absence of cardiac disease and siderosis were risk factors for a delay in LIC measurement >2 years. Patients who never had a cardiac MRI (CMR) T2* measurement were <18 years, had iron intake ≤0·4 mg/kg per day, or a serum ferritin <2500 ng/ml. A history of normal CMR T2* was the main risk factor for a delay in subsequent assessment of >2 years. Deferoxamine (22·8%) was more commonly used in patients with Hepatitis C Virus or high serum creatinine. Deferiprone (20·6%) was less commonly prescribed in patients with elevated alanine aminotransferase; while a deferoxamine + deferiprone combination (17·9%) was more commonly used in patients with serum ferritin >2500 ng/ml or CMR T2* <20 ms. Deferasirox (38·3%) was more commonly prescribed in patients <18 years, but less commonly used in those with heart disease or high iron intake. These observations largely echoed guidelines at the time, although some practices are expected to change in light of evolving evidence.